The effectiveness of Online physics laboratory - Baharuddin, Naemah; Usop @ Yusoff, Habibah; Mat Nawi, Mohd Nazir; Husin, Hafiz; Ishak, Izdihar; Mohd Noor, Mazni (Centre of Foundation Studies, International Islamic University Malaysia, 2021)
The pandemic crisis of COVID-19 has made e-learning mandatory in all Malaysia’s educational institutions including at the Centre for Foundation Studies (CFS), IIUM. In light of this phenomenon, this research is carried out to evaluate the student’s perception on the quality and effectiveness of the online Physics Laboratory delivery at CFS, IIUM. The subject of this research is the students that have enrolled for Physics 1 and 2 subjects in Semester 2, 2020/2021. The online physics laboratory activities were carried out by a group of 4 students and every group submitted their report to the lecturer one day later. This research utilized a quantitative method by giving questionnaires to the students using the Quizizz application involving 325 students. The findings of this research revealed that 85.4% of the students are satisfied with the quality of the lab materials. Narrowing down the students' perception on the laboratory material provided, 85.8% of the students agreed that it was easy to understand and 89.5 % agreed that the information given was clear. These above 80% agreements showed that the quality of the given material is qualified for online learning. Understanding data tabulation is an important step in the process of data analysis. 78.2% respondent agreed that they now have the ability to tabulate experimental data on their own after the online lab session. In terms of completing the laboratory report, only 65% agree that it is easy to compile and submit the report. This is perhaps due to the analysis activity that had to be done in a group. They had to do online discussion, delegating tasks between one another, handwritten every part of the laboratory report, compiled their task and finally handed it over online. Though the process is long, 91.4% agreed that they have enough time to complete the lab report. The survey result shows that learning physics laboratory through the online medium is possible and effective. In future, it is recommended that the online physics laboratory learning should be improvised, especially in variation of data given to students for achieving good quality in student performance and assessment.